Avaliação da empatia nos médicos residentes do Hospital Universitário Alzira VELANO em Alfenas Minas Gerais - PAIVA, Antonio Henrique de (2018)
Introduction: Much is discussed about the importance of empathy in the patient physician relationship. Few studies have evaluated this ability in resident physicians (RPs). Objective: To evaluate the empathy of the resident physicians of the University Hospital Alzira Velano (HUAV), through the Jefferson Scale of Medical Empathy (EJEM), which provides 4 types of scores: General Empathy (EG); Patient Perspective (TP); Compassion (CP) and Ability to Put in Place the Other (LO). Methods: EJEM and a socio-demographic questionnaire were applied to 36 MRs of the HUAV at the beginning of the second semester of 2016, after signing the informed consent form. Results: Statistical analysis by the Mann-Whitney test showed that empathy scores were associated with variables: sex, area of performance (clinical or surgical) and period of residence in progress. For the sex variable, the following findings were found: 1) Female RPs of the 1 st year had higher EG scores than the RPs in the ≥ 2nd year (p = 0.01); 2) RP's females of 1st year had higher TP scores than RPs of ≥ 2nd year (p = 0.03). Regarding the area of performance, 1) the EG scores of the 1 st year RPs were higher compared to the RPs in the ≥ 2nd year, both for the clinical (p = 0.03) and for the surgical area (p = 0.02); 2) RPs of the surgical area had higher TP scores in the 1st year compared to RPs in the ≥ 2nd year (p = 0.01). No association to the factors studied was observed for CP and LO scores. Conclusion: The data show that the empathy scores of the RPs of the final years are lower in relation to the RPs of the 1st year, a fact also verified for female RPs . Our data share the observations of the literature and show the importance of the development of instructional strategies for the teaching of empathy among resident physicians.